Using the Free Fire Game in Building A Bonding Intercultural Social Network Among Players - Asmira, Dewi; Sunusi, Seny Luhriyani; Amin, Fatimah Hidayahni (ELT Worldwide: Journal of English Language Teaching, 2025)
This research explores using the Free Fire game in building a bonding intercultural social network among its players. In an era marked by rapid technological advancement and globalization, the internet has become a platform for diverse cultural interactions, with online games playing a central role. Free Fire, a popular mobile battle royale game, offers a unique environment for players from different cultural backgrounds to connect, collaborate and form social networks. This study uses a qualitative approach with a descriptive research design to investigate language use and the supporting and inhibiting factors in the formation of intercultural social networks through the Free Fire game. Data were collected through participant observation, interviews, and document analysis, focusing on how players use language to interact, communication strategies, and develop friendships. The results show that the importance of effective communication and collaboration in fostering social relationships, with supporting factors such as accessibility, teamwork, and a diverse community of players, as well as hindering factors such as language barriers, cultural differences, and in-game toxicity. This research contributes to the understanding of online gaming as a platform for intercultural exchange and provides insights into how gaming environments such as Free Fire facilitate the creation of cultural social networks.